DETERMINATION OF THE QUALITY INDICATORS OF APPLE JUICE BEVERAGES - Барус, Маріанна; Скрипська, Ольга; Мінтянська, Альона; Білокопита, Галина (SWorldJournal, 2023)
The paper examined the quality of juice drinks according to the organoleptic properties, total and active acidity, content of dry substances, vitamin C using physicochemical methods of analysis.